2021
DOI: 10.1186/s13293-020-00349-w
|View full text |Cite
|
Sign up to set email alerts
|

The associations of hostility and defensiveness with telomere length are influenced by sex and health status

Abstract: Background Shorter telomere length (TL) may indicate premature cellular aging and increased risk for disease. While there is substantial evidence for shorter TL in individuals suffering from psychiatric disorders, data is scarce on maladaptive personality traits related to coronary artery disease (CAD). The purpose of this study was to evaluate the association of TL with hostility and defensiveness in individuals with CAD or other non-cardiovascular illnesses and whether associations were moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Starnino et al [ 61 ] found that patients with stable CAD had a shorter LTL compared with healthy volunteers and people without CVD ( p -value < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starnino et al [ 61 ] found that patients with stable CAD had a shorter LTL compared with healthy volunteers and people without CVD ( p -value < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that in studies of the mean relative LTL in young, middle-aged, and elderly adults, the value of this molecular biomarker decreases not only in relation to the physiological biological aging of the human body but also in relation to the premature development of stable CAD [ 64 ] and the early development of AMI [ 60 ]. At the same time, the most convincing results were obtained in studies of relative LTL in middle-aged and elderly patients with stable CAD [ 55 , 58 , 59 , 61 , 63 , 64 , 65 ]. It seems important from a practical point of view because patients with stable CAD and with shortened relative LTL can have unfavorable prognoses concerning general mortality [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative polymerase chain reaction (qPCR) was used to measure LTL using the modified method (75) of the protocol described by Cawthon (76) as previously reported in Starnino et al (77). This method is based on determining the number of telomere DNA sequences (T) on the number of copies of a control gene (RPLP0, 60S acidic ribosomal protein P0) (S).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative polymerase chain reaction (qPCR) was used to measure TL, using the modified method (Epel et al, 2004 ) of the protocol described by Cawthon ( 2002 ) as previously reported in Starnino et al ( 2021 ). This method is based on determining the number of telomere DNA sequences ( T ) on the number of copies of a control gene (RPLP0, 60S acidic ribosomal protein P0) ( S ).…”
Section: Methodsmentioning
confidence: 99%